Effect of Initial Arch Rib Angle Variation and Arch Height on Structure Performance of Tied Steel Arch Bridge - Dzulkarnain Muhammad Khazruya; Izatulillah Izatulillah; Faiz Razaan Nema; Dzul Fikri Muhammad (Universitas Islam Raden Rahmat, Malang, 2025)
Efficient use of materials in the tied arch bridge can be reach by optimizing it. This article examined initial arch angle and the top height effects. The use of initial angle (20°, 25°, 30°) combined with different top arch height (0,5 – 0,6 meter) is based on rise-span ratio 1:8 – 1:6,67. 9 bridge models are produced from these variations. This study aimed to minimizing deflection and weight for optimizing structural performance, thus decrease steel use also CO₂ emissions for support Indonesia toward SDGs 2045. 3D model was analyzed using FEM (Finite Element Method) Software with a 250 kg mid-span load using the tributary method, which is simulating pedestrian weight transferred through the floor plate and tie chord. Analysis results showed that the arch initial angle and the top height affect the structural performance. With the best performance is showed by type 1.3 with 20° initial angle and top arch height (0,6).